APAKAH KINERJA KEUANGAN MEMEDIASI PENGARUH INTELLECTUAL CAPITAL TERHADAP REAKSI INVESTOR PADA PERUSAHAAN PERBANKAN DI INDONESIA (?) - Crescentiano Agung Wicaksono; Afni Sirait; Heri Susanto (Jurnal Bisnis dan Kewirausahaan, 2020)
Intellectual capital is vital for companies to improve competitiveness. Company stakeholders are starting to realize that intellectual capital is one of the intangible assets that need to be managed properly because it helps companies compete. This study aims to examine financial performance in mediating the effect of intellectual capital on investor reaction. Financial performance is measured using a return on assets, intellectual capital as an independent variable is measured using value-added Intellectual capital (VAICTM) which consists of three components, namely: human capital, structural capital, and relational capital, while investor reactions are measured using abnormal returns. The object of research is the banking sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2018 by the determined purposive sampling. This study uses Structural Equation Modeling (SEM) for data analysis and hypothesis testing, and uses the WarpPLS version 7.0 software to process data. Based on the test results, several conclusions: (a) Intellectual has a positive and significant effect on investor reaction, (b) Intellectual capital has a positive and significant effect on financial performance, (c) financial performance has a positive and significant effect on investor reaction, and (d) financial performance can fully mediate the effect of Intellectual capital on investor reactions.